2021
DOI: 10.3390/biomedicines9111721
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Combined Polyphenols and Micronutrients against Influenza A Virus and SARS-CoV-2 Infection In Vitro

Abstract: Polyphenols have been widely studied for their antiviral effect against respiratory virus infections. Among these, resveratrol (RV) has been demonstrated to inhibit influenza virus replication and more recently, it has been tested together with pterostilbene against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. In the present work, we evaluated the antiviral activity of polydatin, an RV precursor, and a mixture of polyphenols and other micronutrients, named A5+, against influenza viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 43 publications
3
27
0
Order By: Relevance
“…Then, to avoid side effects, we used a concentration of A5 + lower that 30 μM, and based on cell viability assay, we used 10 μM of A5 + for all further experiments. These results also align with the findings of De Angelis et al [ 22 ].…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Then, to avoid side effects, we used a concentration of A5 + lower that 30 μM, and based on cell viability assay, we used 10 μM of A5 + for all further experiments. These results also align with the findings of De Angelis et al [ 22 ].…”
Section: Resultssupporting
confidence: 93%
“…Then, we demonstrated that pretreatment with A5 + significantly reduced the levels of IFN-γ (p < 0.05), IL-1β (not significant), IL-6 (p < 0.001), TNF-α (p < 0.001), and CXCL1 (p < 0.001) compared to cells treated only with 6-OHDA. These data are in agreement with our previous data demonstrating that A5 + reduced IL-6 production in Vero E6 cells infected with Influenza A Virus [22], and further suggest relevant anti-inflammatory properties of A5 + .…”
Section: A5 + Protects From 6-ohda-iduced Neuroinflammationsupporting
confidence: 93%
See 2 more Smart Citations
“…Indeed, the knockdown of individual sirtuins, including SIRT2, has been shown to increase the influenza virus replication ( Koyuncu et al., 2014 ). Moreover, treatment with sirtuin modulators including resveratrol and its derivatives have been shown to control different respiratory viral infections ( Palamara et al., 2005 ; De Angelis et al., 2021 ; Pasquereau et al., 2021 ). In our model, by restoring the deacetylation activity of SIRT2 using an inhibitor of P300 acetyltransferase (C646), viral replication was reduced ( Figure 6A ).…”
Section: Discussionmentioning
confidence: 99%